PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MELALUI PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Manullang, Febriani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2018)
The purpose of this study was to improve the learning outcomes of Mathematics by using PMRI on the fifth grade students of SD Negeri 08 Lembak, South Sumatra. This study uses Classroom Action Research (CAR). Data collection techniques in this study consisted of written tests and observations. The subjects of this study were the students of class VA SD 08 Lembak in the even semester of 2017/2018 school year which consisted of 23 students, consisting of 12 male students and 11 female students. The results showed that using PMRI, there was increased in each cycle. Students are declared complete in learning if they achieve completeness of at least > 60 or a class is declared complete learning if in that class there are 85% of students who get scores above 60. This can be seen from the results of the pre-cycle value of 51.2 increases when the first cycle becomes 64.8 with the percentage of completeness from 17.4% to 60.8%. Then the average in the second cycle increased from the first cycle, from 64.8 to 78.3 with the percentage of completeness from 60.8% to 86.9%. The average activity percentage of students also increased from first cycle to second cycle, from 58.6% to 70.6%. Based on the results of the study it can be concluded that by using Team Quiz's active learning strategy, student learning outcomes can increase, then Team Quiz's active learning strategy can be used as an alternative choice for teachers in the teaching and learning process.